The Neogene of Portugal - Antunes, M. Telles (2010)
After a brief historical introduction, this paper deals with the main concerned geotectonic units: the Lower Tagus and Alvalade basins, the Western and Southern borders, and their infillings. Most of the Neogene events and record concern areas South of the Iberian Central Chain, a nearly inverse situation as that of Paleogene times. In the most important of these units, the Lower Tagus basin, there are quite thick detrital series, mostly marine in its distal part near Lisboa (albeit with several continental intercalations), and mainly continental in its inner part. Sedimentological record is almost complete since Lowermost to Upper Miocene. The richness ofdata (paleontology, isotope chronology, paleoclimate, etc.) it gives and the possibility of direct marine-continental correlations render this basin one of the more interesting ones in Western Europe. Alvalade basin is separated from the previous one by a barrier of Paleozoic rocks. Two transgressions events (Upper Tortonian and Messinian in age) are recorded. Active sedimentation may be correlated to Late Miocene tectonics events. In Algarve, chiefly marine units from Lower to Upper Miocene are well developped. The Lower unit (Lagos-Portimão Formation) is best exposed in Western Algarve, but desappears eastwards. Middle Miocene is not as well known, whereas Upper Miocene main outcrops are in Eastern Algarve. Cacela Formation is remarquable for its beautiful fossils. Sedimentation as a whole refletcts the tectonic activity and in special the evolution of the Algarve flexures. There is scant evidence of post-Lower Miocene volcanism, the latest known in Portugal. Pliocene has not been recognized there beyond doubt. Miocene sediments are much less important to the North of the Central Iberian Chain. Continental beds near Leiria that yielded the well-known "Hisp anotherium fauna" are lower Middle Miocene. Pliocene corresponds to dramatic changes in paleogeography. At Setiibal Peninsula there is some evidence of a minor Lower Pliocene transgression. Continental detrital sediments, often coarse, occupy rather large areas. In Western Portugal between the Setúbal Peninsula and Pombal there is good evidence of a marine Upper Pliocene transgression, followed up by dune sands overlain by marsh clays, diatomites, lignites and boghead levels that can be partly Pleistocene in age.